A teaching progression for squatting exercises - Chiu, L.; Burkhardt, E. (Strength and Conditioning Journal, 2011)
A teaching progression for squatting exercise is presented. The primary exercise in this progression is the plate squat, which encourages proper technique, improves flexibility and strengthens the stabilizing musculature. Use of the plate squat will teach proper positions for the overhead, front, and back squats.